Canine Parvovirus and Its Non-Structural Gene 1 as Oncolytic Agents: Mechanism of Action and Induction of Anti-Tumor Immune Response - Arora, Richa; Malla, Waseem Akram; Tyagi, Arpit; Mahajan, Sonalika; Sajjanar, Basavaraj; Tiwari, Ashok Kumar (Frontiers in Oncology, 2021)
The exploration about the strategies for prevention and treatment of cancer is far from complete. Apart from humans, cancer has gained considerable importance in animals because of increased awareness towards animal health and welfare. Current cancer treatment which includes chemo-radiotherapies is less specific towards tumor cells and end up harming normal healthy cells. Thus, a highly specific therapeutic strategy with minimal side effects is the need of hour. Oncolytic viral gene therapy is one such specific approach to target cancer cells without affecting the normal cells of body. Non structural gene 1 (NS1) of Canine Parvovirus (CPV), involved in viral DNA replication has the capacity to selectively induce apoptosis in cancer cells and cause direct tumor cell lysis. In this review, we discuss the oncolytic properties of Canine Parvovirus (CPV or CPV2), structure of NS1 gene, mechanism of oncolytic action as well as role in inducing an antitumor immune response in different tumor models.